A Multifactorial Approach in Type 2 Diabetes Over 3 Years Decelerates Progression of Subclinical Arterial Disease in Routine Clinical Practice. (November 2021) - Konstantonis, George; Arida, Aikaterini; Aissopou, Evaggelia; Protogerou, Athanasios; Tentolouris, Nikolaοs; Sfikakis, Petros P.; Makrilakis, Konstantinos
The beneficial effect of multifactorial treatment of cardiovascular (CV) risk factors (RFs) in type 2 diabetes (T2D) is well established from randomized clinical trials. We prospectively evaluated the impact of such treatment in a real-world setting, on the development of subclinical arterial damage (SAD), as determined by structural/functional noninvasive biomarkers of vascular pathology (atheromatosis, carotid hypertrophy, arteriosclerosis). We prospectively studied 116 persons with T2D, treated with a multifactorial approach for CV RFs at a tertiary medical center, and 324 individuals without diabetes, for 3.2 years. The primary outcome was changes in vascular biomarkers related to SAD. At baseline, participants in the diabetes group had higher prevalence of SAD. At study end, the changes in clinical, biochemical, and lifestyle characteristics, as well as antihypertensive and lipid-lowering treatments, were comparable between the 2 groups. During follow-up, classical CV RFs (smoking, blood pressure, low-density lipoprotein-cholesterol, triglycerides) and behavioral features were significantly improved in both groups. Multivariate analysis, after adjusting for all classic CV RFs and use of antihypertensive/lipid-lowering therapies, demonstrated that all evaluated SAD biomarkers were similarly changed in the 2 groups. In conclusion, implementation of a multimodality approach of T2D treatment is feasible and efficacious in decelerating progression of SAD in routine clinical practice.